Analisis Laporan Keuangan Melalui Uji Beda Kinerja Keuangan pada PT Phapros Tbk Periode 2020–2024 - Tri Apriliyani; Arditya Dian Andika; Agung Prajanto; Melati Oktafiyani (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
Changes in economic conditions due to the COVID-19 pandemic have created significant dynamics in the financial performance of various companies, including those in the pharmaceutical sector. This study aims to analyze the financial performance of PT Phapros Tbk during the 2020–2024 period and to examine differences in financial performance across the pandemic, transition, and post-pandemic phases. This research employs a quantitative approach using secondary data in the form of quarterly financial statements over five years (20 observations). The analytical methods applied include financial ratio analysis (liquidity, solvency, activity, and profitability ratios), trend analysis using the index number method, DuPont analysis to decompose Return on Equity (ROE), and difference testing using the Friedman Test due to non-normal data distribution based on the Shapiro–Wilk test. The results indicate that activity ratios (Inventory Turnover, Fixed Asset Turnover, and Total Asset Turnover), Quick ratio, and Net Profit Margin show significant differences across periods, while Current ratio, Cash ratio, Debt to Asset Ratio, Debt to Equity Ratio, Return on Investment, and Return on Equity do not show significant differences. Overall, changes in PT Phapros Tbk’s financial performance during the research period are more evident in operational efficiency aspects than in capital structure, indicating that the impact of the pandemic and economic recovery affected certain financial indicators differently.